Green Room Circuit at Paulo VI Campus in Maranhao State University, Brazil - Andréa Aráujo do Carmo; Kelly Fernanda de Sousa Santos; Marcos Eduardo Miranda Santos (Journal of Sustainability Perspectives, 2021)
The implementation of the Environmental Management Advisory at Maranhão State University, in 2015, promoted environmental education actions as a continuous in the institution, and coordinated by the Environmental Management System of the advisory. The approval on the call for the creation of Green Rooms, by the Ministry of Environment, became this university qualified in 2018 to have a Green Room in its space, constituting a space for environmental interactions. Thus, the objective was to discuss the actions developed in 2018. Having a Circuit format, the Green Room of this academy (Green Room Circuit at Paulo VI Campus), in the year in question, four visits were made, with activities scheduled in the Fishery and Aquatic Ecology laboratories, Zoology laboratory, Botanical Collection (Rosa Mochel), Agroecological Trail and seedling workshops. Totalizing 109 participants, 33% were from the capital and 67% from the metropolitan region of Sao Luis and other municipalities of Maranhão state, northeast of Brazil. Therefore, the Green Room Circuit of Paulo VI Campus was faced as a potentializer and dynamizer, for the development of actions that contribute to a sustainable awareness among its participants.